Mawad al-Aqyisah dalam Karya Abkar al-Afkar oleh al-Amidi: Analisis dan Terjemahan: Mawad al-Aqyisah in Abkar al-Afkar by al-Amidi: An Analysis and Translation - Ibrahim, Ruzaimi; Hamat, Mohd Fauzi; Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The study of mawad al-aqyisah in logic gained attention after it was brought into the tradition of Islamic knowledge. It includes part of Ibn Sina’s epistemological discourse through his work, al-Isharat wa al-Tanbihat and al-Ghazali through some of his logical works such as Maqasid al-Falasifah, Mi‘yar al-‘Ilm and others. As a Muslim scholar of the sixth century AH, al-Amidi, who emerged after Ibn Sina and al-Ghazali, also discussed the topic through his own preparation and perspective. This study focuses on the analysis of the mawad al-aqyisah debate put forward by al-Amidi, as well as its comparison with the debates of previous logicians such as Ibn Sina and al-Ghazali. This article also explains the importance of the mawad al-aqyisah debate in logic and its categorization pattern. This study uses a content analysis method based on his work Abkar al-Afkar and aims to highlight al-Amidi’s thinking in this debate. This study concludes that al-Amidi has injected some new ideas into the topic of mawad al-aqyisah in a way of categorization and classification different from previous figures. The contribution of his thinking is also able to expand the scope and application of mawad al-aqyisah in the structure of Islamic epistemology, where it plays an important role in helping a person achieve definite knowledge and launch the process of filtering facts and information.